The baron's honourable daughter [large type] - Morris, Lynn, 1954- (Center Point Large Print, 2014)
When her stepfather suddenly dies, Valeria Segrave finds she must take charge of her grieving mother and the vast estate which now belongs to her six-year-old half brother, the new Earl of Maledon. Though capable, Valeria is frustrated to find each day brings a new struggle as she tries to establish her authority with servants, stewards, and solicitors --all men. As a young woman with no blood relation to the earl, they are all too ready to dismiss her. Much to her chagrin, she must rely on the assistance of her stepfather's distant kinsman, Alastair, Lord Hylton. He is handsome and noble, and Valeria senses under the veneer of his gentlemanly behavior that she never measures up to his expectations of a refined lady. In light of that, accepting his help and feeling under a burden of gratitude to him is almost unbearable. Even when Valeria leaves the country estate for the glittering London Season, where she gets into a series of escapades, Lord Hylton is always there to witness, criticize, and correct her behavior. But if Alastair insists on engaging in a battle of wits and wills with the lively Valeria, she'll stop at nothing to prove that he's met his match.